2021
DOI: 10.1136/archdischild-2020-321273
|View full text |Cite
|
Sign up to set email alerts
|

Viability and thresholds for treatment of extremely preterm infants: survey of UK neonatal professionals

Abstract: BackgroundDecisions about treatments for extremely preterm infants (EPIs) born in the ‘grey zone’ of viability can be ethically complex. This 2020 survey aimed to determine views of UK neonatal staff about thresholds for treatment of EPIs given a recently revised national Framework for Practice from the British Association of Perinatal Medicine.MethodsThe online survey requested participants indicate the lowest gestation at which they would be willing to offer active treatment and the highest gestation at whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
0
17
0
1
Order By: Relevance
“…Sixty-eight per cent were female and 40% had more than 16 years’ experience working with EPI ( online supplemental table 2 ). 5 Ninety-five per cent reported having read the revised BAPM framework and 89% indicated that they were currently using it in their clinical practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-eight per cent were female and 40% had more than 16 years’ experience working with EPI ( online supplemental table 2 ). 5 Ninety-five per cent reported having read the revised BAPM framework and 89% indicated that they were currently using it in their clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…The methods of the wider survey have been described previously. 5 Participants were three groups of UK neonatal professionals involved in antenatal decision making around management of EPIs; consultants, middle grade trainee doctors (‘registrars’) and advance neonatal nurse practitioners (ANNPs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitudes of care providers towards the outcomes of babies born at the margins of viability were shown to influence the perinatal care of pregnancies at 22-24 weeks gestation and subsequent neonatal outcomes [8][9][10][11][12][13][14][15][16][17]. These attitudes are however changing, as outcome data from recent publications suggest survival and outcome data for babies born at 22 weeks gestation-similar to what was achieved in the early 1990s with babies born at 24 weeks gestation [18].…”
Section: Historical Perspectivementioning
confidence: 99%
“…Dieser Ansatz wird von anderen Autoren kritisiert und international unterschiedlich gehandhabt (Cummings und Committee on Fetus and Newborn 2015; Lantos 2019). Festzuhalten bleibt, dass Ärztinnen und Ärzte sehr unterschiedliche und sich ändernde Ansichten darüber haben, welche kindliche Prognose ausreichend ist, um lebenserhaltende Maßnahmen nach einer frühen Frühgeburt zu rechtfertigen (Wilkinson et al 2018;Di Stefano et al 2021). Manchmal wird angeführt, Eltern befänden sich in einer Art Ausnahmesituation, die schwerwiegende und weitreichende Entscheidungen zu sehr erschwere, oder, dass Eltern die Bürde der Verantwortung dieser schweren Entscheidungen nicht tragen können oder wollen.…”
Section: Akteur*innen Der Entscheidungsfindungunclassified